A fused heterocyclic compound and application thereof, and an organic electroluminescent device comprising the same
By designing fused heterocyclic compounds and introducing R13 and R14 units to suppress intermolecular aggregation, the problems of low efficiency and short lifetime of blue light-emitting doped materials were solved, achieving a narrow emission spectrum with high efficiency and long lifetime, which is suitable for organic electroluminescent devices.
Patent Information
- Application Number
- CN202310093341.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-30
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-01-30
AI Technical Summary
Existing blue luminescent doped materials suffer from low efficiency, short lifetime, and insufficient color purity, and are prone to intermolecular aggregation, leading to reduced luminescence efficiency and lifetime.
A fused heterocyclic compound was designed. By introducing R13 and R14 units on the core unit to suppress π-π interactions, a rigid planar core unit was formed, which improved luminescence efficiency and suppressed intermolecular aggregation quenching, thus achieving a narrow emission spectrum.
It significantly improves the luminous efficiency and lifetime of the material, narrows the full width at half maximum (FWHM) of the spectrum of the electroluminescent device, and improves the color purity, thus meeting the requirements of high-performance luminescent materials.
Smart Images

Figure CN117209517B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic electroluminescence technology, and in particular to a novel organic compound and its applications, as well as an organic electroluminescent device containing the compound. Background Technology
[0002] Organic light-emitting devices (OLEDs) are current-driven thin-film devices with a sandwich-like structure, consisting of one or more layers of organic functional materials sandwiched between the anode and cathode. OLEDs are characterized by self-emission, wide viewing angle, wide color gamut, short response time, high luminous efficiency, low operating voltage, low cost, and simple manufacturing process. They are currently widely used in display products such as televisions, smartphones, tablets, automotive displays, and lighting, and will be further applied in creative display products such as large-size displays and flexible screens.
[0003] Organic optoelectronic materials used in OLED devices can be divided into light-emitting layer materials and auxiliary functional layer materials. Among them, light-emitting layer materials include guest materials (also known as light-emitting materials or doped materials) and host materials (also known as matrix materials). Light-emitting materials are divided into fluorescent materials, phosphorescent materials and thermally activated delayed fluorescence materials according to different energy transfer methods. Auxiliary functional layer materials are further divided into electron injection materials, electron transport materials, hole blocking materials, and hole injection materials according to different electron or hole transport speeds.
[0004] The luminescent dopants used in the luminescent layer have a decisive impact on the color, efficiency, and stability of electroluminescent devices. However, luminescent dopant materials with high efficiency and narrow emission are still in short supply. Current blue luminescent dopants suffer from low efficiency, short lifetime, and insufficient color purity. For example, boron nitride compounds in the literature (Adv. Mater. 2016, 28, 2777–2781) can achieve a narrow half-maximum width at half maximum (WHM) due to the multiple resonance effect of the boron nitride structure. However, their molecular structure results in low luminescence efficiency and they are prone to intermolecular aggregation, leading to reduced efficiency and lifetime.
[0005] Therefore, there is an urgent need in this field to develop a class of OLED luminescent materials that possess high luminous efficiency and a narrow emission spectrum, while effectively suppressing intermolecular aggregation. Such materials offer advantages such as high efficiency, long lifetime, and narrow emission spectrum when applied in organic electroluminescent devices.
[0006] Existing technical documents
[0007] Non-patent literature 1: Adv. Mater. 2016, 28, 2777–2781 Summary of the Invention
[0008] This invention aims to solve the aforementioned technical problems. In this invention, on the one hand, as illustrated, the structure within the circle constructs a rigid planar core unit, thereby facilitating the acquisition of high luminous efficiency and a narrow half-width emission spectrum. On the other hand, through the R outside the core... 13 R 14 The unit effectively suppresses aggregation quenching and excitocomplex formation caused by intermolecular π-π interactions. This significantly improves the luminescent properties of the material in solid-state thin films, thereby enhancing the efficiency and lifetime of electroluminescent devices.
[0009]
[0010] Specifically, the present invention provides: 1) a fused heterocyclic compound, wherein the fused heterocyclic compound is represented by the following general formula (1) or general formula (2):
[0011]
[0012] Where Y represents NR 21 O atoms, S atoms, Se atoms;
[0013] R1~R 12 Each is independently selected from: hydrogen, deuterium, cyano, halogen, substituted or unsubstituted alkyl with 1 to 50 carbon atoms, substituted or unsubstituted alkenyl with 1 to 20 carbon atoms, substituted or unsubstituted alkynyl with 3 to 50 carbon atoms, substituted or unsubstituted alkoxy with 1 to 50 carbon atoms, substituted or unsubstituted aryloxy with 1 to 50 carbon atoms, substituted or unsubstituted silyl with 1 to 30 carbon atoms, substituted or unsubstituted aryl with 6 to 50 carbon atoms, substituted or unsubstituted heteroaryl with 2 to 50 carbon atoms, substituted or unsubstituted arylamino with 6 to 50 carbon atoms, substituted or unsubstituted alkylamino with 1 to 30 carbon atoms, and substituted or unsubstituted arylsilyl with 6 to 50 carbon atoms;
[0014] R1~R 12 They can optionally bond to each other to form substituted or unsubstituted saturated or unsaturated rings;
[0015] R 13 R 14Each of the following is independently selected from hydrogen atoms, deuterium atoms, substituted silyl groups, substituted or unsubstituted alkyl groups with 1 to 50 carbon atoms, substituted or unsubstituted alkenyl groups with 1 to 20 carbon atoms, substituted or unsubstituted alkynyl groups with 1 to 50 carbon atoms, substituted or unsubstituted fluoroalkyl groups with 1 to 20 carbon atoms, substituted or unsubstituted fluoroalkoxy groups with 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl groups with 3 to 50 carbon atoms, substituted or unsubstituted cycloaryl groups with 6 to 50 carbon atoms, and substituted or unsubstituted heteroaryl groups with 5 to 40 carbon atoms.
[0016] R 13 and R 14 They may optionally bond to each other to form substituted or unsubstituted saturated or unsaturated rings;
[0017] R 21 Selected from: alkyl groups with 1 to 50 substituted or unsubstituted carbon atoms, alkenyl groups with 1 to 20 substituted or unsubstituted carbon atoms, cycloalkyl groups with 3 to 50 substituted or unsubstituted cyclic carbon atoms, silyl groups with 1 to 30 substituted or unsubstituted carbon atoms, fluoroalkyl groups with 1 to 20 substituted or unsubstituted carbon atoms, aryl groups with 6 to 50 substituted or unsubstituted carbon atoms, heteroaryl groups with 2 to 50 substituted or unsubstituted carbon atoms, and aromatic amino groups with 6 to 50 substituted or unsubstituted carbon atoms.
[0018] R 21 Optionally, it can be bonded to adjacent groups to form substituted or unsubstituted saturated or unsaturated rings.
[0019] 2) The fused heterocyclic compound according to 1), characterized in that Y is an O, S or Se atom.
[0020] 3) The fused heterocyclic compound according to 1), characterized in that R1 to R 14Each and every one is independently selected from: substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted n-propyl, substituted or unsubstituted isopropyl, substituted or unsubstituted n-butyl, substituted or unsubstituted isobutyl, substituted or unsubstituted sec-butyl, substituted or unsubstituted tert-butyl, substituted or unsubstituted 2-methylbutyl, substituted or unsubstituted n-pentyl, substituted or unsubstituted sec-pentyl, substituted or unsubstituted trifluoromethyl, substituted or unsubstituted pentafluoroethyl, substituted or unsubstituted 2,2,2-trifluoroethyl, substituted or unsubstituted vinyl, substituted or unsubstituted propenyl, substituted or unsubstituted n-butenyl, substituted or unsubstituted isobutenyl, substituted or unsubstituted n-pentenyl, substituted or unsubstituted isopentenyl, substituted or Unsubstituted neopentenyl, substituted or unsubstituted ethynyl, substituted or unsubstituted cyclopropyl, substituted or unsubstituted cyclobutyl, substituted or unsubstituted cyclopentyl, substituted or unsubstituted cyclohexyl, substituted or unsubstituted adamantyl, substituted or substituted methylsilyl, substituted or unsubstituted phenylsilyl, substituted or unsubstituted phenyl, substituted or unsubstituted pyridyl, substituted or unsubstituted biphenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted anthraceneyl, substituted or unsubstituted phenanthryl, substituted or unsubstituted indene, substituted or unsubstituted fluorenyl, substituted or unsubstituted spirodifluorenyl, substituted or unsubstituted indofluorenyl, substituted or unsubstituted fluoranyl, substituted or unsubstituted pyrene, substituted or unsubstituted perylyl, substituted or unsubstituted alkyl, substituted or unsubstituted tetraphenyl, substituted or unsubstituted benzothiophene, substituted or unsubstituted benzofuran, substituted or unsubstituted dibenzothiophene, substituted or unsubstituted dibenzothiophene, substituted or unsubstituted dibenzofuran, substituted or unsubstituted dibenzoselenophene, substituted or unsubstituted carbazolyl, substituted or unsubstituted indolyl, substituted or unsubstituted diphenylamino, substituted or unsubstituted triphenylphosphoxy, substituted or unsubstituted benzonitrile, substituted or unsubstituted triazine, substituted or unsubstituted pyrazinyl;
[0021] R1~R 12 The substituent group may also be selected from any one or more of the following groups: hydrogen atom, deuterium atom, fluorine atom, chlorine atom, bromine atom.
[0022] 4) The fused heterocyclic compound according to 1), characterized in that, the R 13 and R 14 They bond together to form rings as shown in equations (2-1) to (2-7):
[0023]
[0024] Among them, R 31 ~R 39The substituents are independently selected from hydrogen atoms, deuterium atoms, halogen atoms, substituted silyl groups, substituted or unsubstituted alkyl groups with 1 to 50 carbon atoms, substituted or unsubstituted alkenyl groups with 1 to 20 carbon atoms, substituted or unsubstituted alkoxy groups with 1 to 50 carbon atoms, substituted or unsubstituted fluoroalkyl groups with 1 to 20 carbon atoms, substituted or unsubstituted fluoroalkoxy groups with 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl groups with 3 to 50 cyclic carbon atoms, substituted or unsubstituted aryl groups with 6 to 50 cyclic carbon atoms, and substituted or unsubstituted monovalent heterocyclic groups with 5 to 50 cyclic carbon atoms.
[0025] 5) The fused heterocyclic compound according to 1), characterized in that the R 13 and R 14 It is independently selected from alkyl groups having 1 to 50 carbon atoms, substituted or unsubstituted, and aryl groups having 6 to 50 cyclic carbon atoms, substituted or unsubstituted.
[0026] 6) The fused heterocyclic compound according to 1), characterized in that the R 13 and R 14 They bond with each other to form cyclobutane with 4 to 50 substituted or unsubstituted carbon atoms, cyclopentane with 5 to 50 substituted or unsubstituted carbon atoms, cyclohexane with 6 to 50 substituted or unsubstituted carbon atoms, and adamantane.
[0027] 7) The fused heterocyclic compound according to 1), characterized in that the fused heterocyclic compound is selected from the following structures:
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037] 8) An organic electroluminescent device, wherein the organic electroluminescent device comprises an anode, a cathode, and at least one organic thin film located between the anode and the cathode, the organic thin film containing any one of the compounds in 1) to 7).
[0038] 9) The organic electroluminescent device according to 8), wherein the organic thin film comprises any one or at least two combinations of a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, an exciton blocking layer, a hole blocking layer, an electron transport layer, and an electron injection layer, and at least one of the light-emitting layers contains any one of the compounds in 1) to 7).
[0039] 10) An organic electroluminescent device according to 8) or 9), wherein the compound is used as a fluorescent material of the light-emitting layer in the organic electroluminescent device.
[0040] Compared with the prior art, the beneficial effects of the present invention are: the electroluminescence spectrum of the OLED device prepared by the compound of the present invention has a narrow half-width, which greatly improves the luminous efficiency and color purity of the material of multiple resonance-thermal activated delayed fluorescence; and it has low start-up voltage, high luminous efficiency and better lifespan, which can meet the current display industry's requirements for high-performance luminescent materials and shows good application prospects. Attached Figure Description
[0041] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:
[0042] Figure 1 The diagram below shows the structure of an organic electroluminescent device using the compounds of this invention. The meanings of each layer in the device structure are as follows:
[0043] 1. Transparent substrate layer, 2. ITO anode layer, 3. Hole injection layer, 4. Hole transport layer A, 5. Hole transport layer B (or electron blocking layer), 6. Light-emitting layer, 7. Electron transport layer B (or hole blocking layer), 8. Electron transport layer A, 9. Electron injection layer, 10. Cathode reflective electrode layer. Detailed Implementation
[0044] The principles and features of the present invention will be further illustrated below with several synthetic embodiments. The embodiments are only used to explain the present invention, but are not intended to limit the scope of the present invention.
[0045] The following are the methods for synthesizing specific compounds of formula (1).
[0046] Synthesis Examples
[0047] Synthesis Example 1: Synthesis of Chemical 2
[0048]
[0049] Synthesis of intermediate 1a: 2.98 g (20 mmol) of 4-tert-butylaniline, 5.38 g (20 mmol) of 3-bromo-5-tert-butylbenzothiophene, 0.91 g (1 mmol) of tris(dibenzylacetone)dipalladium, 1.76 g (8 mmol) of tri-tert-butylphosphine, and 2.88 g (30 mmol) of sodium tert-butoxide were added to 60 mL of toluene. The mixture was purged under nitrogen protection and reacted at 80 °C for 2 h. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 4.38 g of intermediate 1a was obtained by silica gel column chromatography, yielding 65%. The molecular weight was determined by mass spectrometry to be m / z = 336.2 [MH]. - ].
[0050]
[0051] Synthesis of intermediate 1b: 14.5 g (50 mmol) of 2-bromoiodobenzene, 22.7 g (50 mmol) of 2,3-dichloroaniline, 0.91 g (1 mmol) of tris(dibenzylacetone)dipalladium, 4.4 g (8 mmol) of 1,1'-bis(diphenylphosphine)ferrocene, and 5.76 g (60 mmol) of sodium tert-butoxide were added to 100 mL of toluene. The mixture was refluxed overnight at 120 °C under nitrogen protection. After cooling to room temperature, it was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 12.9 g of intermediate 1b, with a yield of 82%. The molecular weight was determined by mass spectrometry to be m / z = 314.9 [MH]. - ].
[0052] Synthesis of intermediate 1c: 12.5 g (40 mmol) of intermediate 1a, 0.066 g (0.4 mmol) of palladium acetate, 0.23 g (0.8 mmol) of tricyclohexylphosphine, and 10.9 g (80 mmol) of potassium carbonate were weighed and added to 60 mL of DMF. The mixture was purged under nitrogen protection and reacted at 120 °C for 4 h. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 7.9 g of intermediate 1c was obtained by silica gel column chromatography, yielding 84%. The molecular weight was determined by mass spectrometry to be m / z = 234.2 [MH]. - ].
[0053] Synthesis of Intermediate 1d: 7.06 g (30 mmol) of Intermediate 1b, 9.17 g (35 mmol) of methyl 2-iodobenzoate, 0.38 g (6 mmol) of copper powder, and 10.9 g (80 mmol) of potassium carbonate were weighed and added to 60 mL of o-dichlorobenzene. The mixture was purged under nitrogen protection and reacted at 180 °C for 24 h. After cooling to room temperature, dichlorobenzene was removed by vacuum distillation, followed by extraction with ethyl acetate / water, drying over anhydrous sodium sulfate, and concentration by rotary evaporation. Approximately 7.53 g of Intermediate 1d was obtained by silica gel column chromatography, yielding 68%. The molecular weight was determined by mass spectrometry to be m / z = 369.3 [M].+ ].
[0054] Synthesis of intermediate 1e: 7.38 g (20 mmol) of intermediate 1c was weighed and dissolved in 60 mL of anhydrous tetrahydrofuran under nitrogen protection. 25 mL of a 2.0 M, 50 mmol THF solution of methyl magnesium bromide was added dropwise, and the reaction was carried out at room temperature for 1 h. The reaction was quenched with water, extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. The solution was dissolved in 50 mL of dichloromethane, and 2.8 g (20 mmol) of boron trifluoride diethyl ether solution was added dropwise. The reaction was carried out at room temperature for 1 h. The reaction was quenched with water, neutralized with sodium carbonate solution, extracted with dichloromethane / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 6.18 g of intermediate 1e was obtained by silica gel column chromatography, yielding 88%. The molecular weight was determined by mass spectrometry to be m / z = 351.2 [M]. + ].
[0055] Synthesis of intermediate 1f: 7.02 g (20 mmol) of intermediate 1e, 6.74 g (20 mmol) of intermediate 1a, 0.91 g (1 mmol) of tris(dibenzylacetone)dipalladium, 1.76 g (8 mmol) of tri-tert-butylphosphine, and 2.88 g (30 mmol) of sodium tert-butoxide were added to 60 mL of toluene. The mixture was refluxed overnight at 100 °C under nitrogen protection. After cooling to room temperature, it was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 8.22 g of intermediate 1f, with a yield of 63%. The molecular weight was determined by mass spectrometry to be m / z = 652.4 [M]. + ].
[0056] Synthesis of Chemical 2: 6.52 g (10 mmol) of intermediate 1f was weighed and dissolved in 50 mL of dry anhydrous xylene. Under nitrogen protection, 16.7 mL of tert-butyllithium solution (20 mmol, 1.2 M) was added dropwise at 0 °C, and the mixture was heated to 60 °C and stirred for 1 h. The mixture was then cooled to room temperature, and 7.5 g (30 mmol) of boron tribromide was added. The mixture was stirred at room temperature for 0.5 h. Then, 5.16 g (40 mmol) of diisopropylethylamine was added, and the mixture was heated to 140 °C and reacted for 6 h. The reaction was stopped, cooled to room temperature, and slowly added to sodium carbonate solution to neutralize to neutral. The mixture was extracted three times with dichloromethane, and the organic phase was collected. The solvent was evaporated, and the mixture was separated by silica gel column chromatography. Recrystallization from dichloromethane and ethanol yielded 0.75 g of the target product. The product was a yellow solid with a yield of 12%, and the molecular weight was determined by mass spectrometry to be m / z = 626.4 [M]. + ]
[0057] Synthesis Example 2: Synthesis of Chemical 7
[0058]
[0059] Synthesis of intermediate 2a: 4-tert-butylaniline in the synthesis of intermediate 1a was replaced with 3-phenyl-5-tert-butylaniline. Under the same reaction conditions, 5.11 g of intermediate 2b was obtained with a yield of 62%. The molecular weight was determined by mass spectrometry to be m / z = 412.2 [M+].
[0060]
[0061] Synthesis of intermediate 2b: 7.05 g (30 mmol) of intermediate 1d, 9.87 g (35 mmol) of 2-bromoiodobenzene, 0.38 g of copper powder (0.14 g, 6 mmol), and 10.9 g (80 mmol) of potassium carbonate were weighed and added to 60 mL of o-dichlorobenzene. The mixture was purged under nitrogen protection and reacted at 180 °C for 24 h. After cooling to room temperature, dichlorobenzene was removed by vacuum distillation, followed by extraction with ethyl acetate / water, drying over anhydrous sodium sulfate, and concentration by rotary evaporation. Approximately 4.1 g of intermediate 2b was obtained by silica gel column chromatography, yielding 35%. The molecular weight was determined by mass spectrometry to be m / z = 388.9 [M]. + ].
[0062] Synthesis of intermediate 2c: 3.9 g (10 mmol) of intermediate 2b was dissolved in 30 mL of anhydrous THF. Under nitrogen protection at -70 °C, 4.0 mL (2.5 M, 10 mmol) of n-butyllithium hexane solution was added dropwise. The reaction was allowed to proceed at low temperature for 0.5 h, then 1.80 g (10 mmol) of 9-fluorenone was added, and the reaction was allowed to proceed at low temperature for 1 h, followed by natural return to room temperature for 2 h. The reaction was quenched with water, extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. The solution was dissolved in 50 mL of dichloromethane, and 1.4 g (10 mmol) of boron trifluoride diethyl ether solution was added dropwise. The reaction was allowed to proceed at room temperature for 1 h. The reaction was quenched with water, neutralized with sodium carbonate solution, extracted with dichloromethane / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Intermediate 2c was separated by silica gel column chromatography to obtain approximately 3.6 g, with a yield of 76%. The molecular weight was determined by mass spectrometry to be m / z = 473.1 [M]. + ].
[0063] Synthesis of intermediate 2d: 4.74 g (10 mmol) of intermediate 2c, 4.14 g (10 mmol) of intermediate 2a, 0.45 g (0.5 mmol) of tris(dibenzylacetone)dipalladium, 0.88 g (4 mmol) of tri-tert-butylphosphine, and 1.44 g (15 mmol) of sodium tert-butoxide were added to 30 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 100 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 5.78 g of intermediate 2d, with a yield of 68%. The molecular weight was determined by mass spectrometry to be m / z = 850.4 [M]. + ].
[0064] Synthesis of Chemical 7: Replacing intermediate 1f with intermediate 2d in the synthesis of Chemical 2, under the same reaction conditions, yielded 1.07 g of the target product, 13% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 824.4 [M]. + ].
[0065] Synthesis Example 3: Synthesis of Chemical 8
[0066]
[0067] Synthesis of intermediate 3a: 3.9 g (10 mmol) of intermediate 2b was dissolved in 30 mL of anhydrous THF. Under nitrogen protection at -70 °C, 4.0 mL (2.5 M, 10 mmol) of n-butyllithium hexane solution was added dropwise. The reaction was allowed to proceed at low temperature for 0.5 h, then 1.96 g (10 mmol) of xanthone was added, and the reaction was allowed to proceed at low temperature for 1 h, followed by natural return to room temperature for 2 h. The reaction was quenched with water, extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. The solution was dissolved in 30 mL of dichloromethane, and 1.4 g (10 mmol) of boron trifluoride diethyl ether solution was added dropwise. The reaction was allowed to proceed at room temperature for 1 h. The reaction was quenched with water, neutralized with sodium carbonate solution, extracted with dichloromethane / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Intermediate 3a was separated by silica gel column chromatography, yielding approximately 3.62 g (74%). The molecular weight was determined by mass spectrometry to be m / z = 489.1 [M]. + ].
[0068] Synthesis of intermediate 3b: 4.89 g (10 mmol) of intermediate 3a, 4.14 g (10 mmol) of intermediate 2a, 0.45 g (0.5 mmol) of tris(dibenzylacetone)dipalladium, 0.88 g (4 mmol) of tri-tert-butylphosphine, and 1.44 g (15 mmol) of sodium tert-butoxide were added to 30 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 100 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 5.54 g of intermediate 3b, with a yield of 64%. The molecular weight, determined by mass spectrometry, was m / z = 866.4 [M]. + ].
[0069] Synthesis of Chemical 8: Replacing intermediate 1f with intermediate 3b in the synthesis of Chemical 2, under the same reaction conditions, yielded 1.01 g of the target product, 12% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 840.4 [M]. + ].
[0070] Synthesis Example 4: Synthesis of Chemical 52
[0071]
[0072] Synthesis of intermediate 4a: 4.98 g (20 mmol) of 2-iodonitrobenzene, 5.58 g (20 mmol) of 2,4-dichlorophenylboronic acid, 0.6 g (0.5 mmol) of tetrakis(triphenylphosphine)palladium, and 4.08 g (30 mmol) of potassium carbonate were weighed and added to 60 mL of toluene, 15 mL of ethanol, and 15 mL of water. The mixture was purged under nitrogen protection and reacted at 80 °C for 8 h. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Interval separation using silica gel column chromatography yielded approximately 5.27 g of intermediate 5a, with a yield of 85%. Mass spectrometry determined the molecular weight to be m / z = 311.0 [M+].
[0073] Synthesis of intermediate 4b: 6.2 g (20 mmol) of intermediate 2a and 13.1 g (50 mmol) of triphenylphosphine were weighed and added to 50 mL of dichlorobenzene. The mixture was purged under nitrogen protection and reacted at 180 °C for 18 h. After cooling to room temperature, dichlorobenzene was removed by vacuum distillation, followed by ethyl acetate / water extraction, drying over anhydrous sodium sulfate, and concentration by rotary evaporation. Approximately 4.94 g of intermediate 4b was obtained by silica gel column chromatography, yielding 76%. The molecular weight was determined by mass spectrometry to be m / z = 323.9 [MH]. - ].
[0074] Synthesis of intermediate 4c: 3.24 g (10 mmol) of intermediate 4b, 2.1 g (12 mmol) of 2-bromofluorobenzene, and 6.5 g (20 mmol) of cesium carbonate were weighed and added to 30 mL of DMF. The mixture was purged under nitrogen protection and reacted at 150 °C for 12 h. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 3.7 g of intermediate 4c was obtained by silica gel column chromatography, yielding 85%. The molecular weight was determined by mass spectrometry to be m / z = 434.9 [M]. + ].
[0075] Synthesis of intermediate 4d: Replacing intermediate 2b with intermediate 4c in the synthesis of intermediate 2c, under the same reaction conditions, yielded 4.23 g of the target product, 82% yield, as a white solid. Mass spectrometry analysis showed a molecular weight of m / z = 517.1 [M]. + ].
[0076] Synthesis of intermediate 4e: 5.17 g (10 mmol) of intermediate 4d, 3.37 g (10 mmol) of intermediate 1a, 0.45 g (0.5 mmol) of tris(dibenzylacetone)dipalladium, 0.88 g (4 mmol) of tri-tert-butylphosphine, and 1.44 g (15 mmol) of sodium tert-butoxide were added to 30 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 80 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 4.18 g of intermediate 4e, with a yield of 54%. The molecular weight, determined by mass spectrometry, was m / z = 774.4 [M]. + ].
[0077] Synthesis of intermediate 4f: 3.87 g (5 mmol) of intermediate 4e, 1.29 g (5.5 mmol) of m-di-tert-butylphenylboronic acid, 0.22 g (0.25 mmol) of tris(dibenzylacetone)dipalladium, 0.42 g (2 mmol) of tri-tert-butylphosphine, and 3.26 g (10 mmol) of potassium phosphate were added to 30 mL of dioxane and 5 mL of water. The mixture was purged under nitrogen protection and reacted overnight at 100 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 4.04 g of intermediate 4e (87% yield), with a molecular weight of m / z = 928.4 [M]. + ].
[0078] Synthesis of Chemical 52: 5.57 g (6 mmol) of intermediate 4f and 3.0 g (12 mmol) of boron tribromide were weighed and added to 30 mL of dichlorobenzene. The reaction was carried out under nitrogen protection at 180 °C for 20 h. After cooling to room temperature, the mixture was neutralized in sodium carbonate solution, extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Dichlorobenzene was removed by vacuum distillation, followed by silica gel column chromatography and recrystallization from dichloromethane / methanol to obtain approximately 0.22 g of the target molecule, with a yield of 4%. The molecular weight was determined by mass spectrometry to be m / z = 936.6 [M]. + ].
[0079] Synthesis Example 5: Synthesis of Chemical 59
[0080]
[0081] Synthesis of intermediate 5a: Replacing di-tert-butylphenylboronic acid with dibenzofuran 2-boronic acid in the synthesis of intermediate 4f, under the same reaction conditions, yielded 4.12 g of the target product, 91% yield, as a white solid. Mass spectrometry determined the molecular weight to be m / z = 906.5 [M]. + ].
[0082] Synthesis of Chemical 59: Replacing intermediate 4f with intermediate 5a in the synthesis of Chemical 52, under the same reaction conditions, yielded 0.36 g of the target product, 6% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 914.5 [M]. + ].
[0083] Synthesis Example 6: Synthesis of Chemical 50
[0084]
[0085] Synthesis of intermediate 6a: 3.88 g (5 mmol) of intermediate 4e, 1.13 g (5 mmol) of 4-tert-butyldiphenylamine 1a, 0.22 g (0.25 mmol) of tris(dibenzylacetone)dipalladium, 0.44 g (2 mmol) of tri-tert-butylphosphine, and 0.76 g (8 mmol) of sodium tert-butoxide were added to 20 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 120 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 3.76 g of intermediate 6a, with a yield of 78%. The molecular weight, determined by mass spectrometry, was m / z = 963.5 [M]. + ].
[0086] Synthesis of Chemical 50: Replacing intermediate 4f with intermediate 6a in the synthesis of Chemical 52, under the same reaction conditions, yielded 0.41 g of the target product, 7% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 971.5 [M]. + ].
[0087] Synthesis Example 7: Synthesis of Chemical 115
[0088]
[0089] Synthesis of intermediate 7a: 3.26 g (10 mmol) of dibromocarbazole, 3.44 g (21 mmol) of 2-isopropylphenylboronic acid, 0.22 g (0.25 mmol) of tris(dibenzylacetone)dipalladium, 0.42 g (2 mmol) of tri-tert-butylphosphine, and 9.8 g (30 mmol) of potassium phosphate were added to 40 mL of dioxane and 8 mL of water. The mixture was purged under nitrogen protection and reacted overnight at 100 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Interval separation by silica gel column chromatography yielded approximately 3.51 g of intermediate 7a, with a yield of 87%. The molecular weight was determined by mass spectrometry to be m / z = 402.3 [MH]. - ].
[0090] Synthesis of intermediate 7b: 4.02 g (10 mmol) of intermediate 7a, 2.66 g (11 mmol) of 1-bromo-3,4-dichloro-2-fluorobenzene, and 6.52 g (20 mmol) of cesium carbonate were weighed into 30 mL of DMF. The mixture was refluxed at 150 °C for 12 h under nitrogen protection, purged, and nitrogen-protected. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, washed with water, concentrated by rotary evaporation, and separated by silica gel column chromatography to obtain 5.25 g of the target product (84% yield). The molecular weight was determined by mass spectrometry to be m / z = 625.2 [M]. + ].
[0091] Synthesis of intermediate 7c: 6.25 g (10 mmol) of intermediate 7b was dissolved in 40 mL of anhydrous THF. Under nitrogen protection at -70 °C, 4.0 mL (2.5 M, 10 mmol) of n-butyllithium hexane solution was added dropwise. The reaction was allowed to proceed at low temperature for 0.5 h, followed by the addition of 0.58 g (10 mmol) of anhydrous acetone. The reaction was allowed to proceed at low temperature for 1 h, then allowed to return to room temperature for 2 h. The reaction was quenched with water, extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. The solution was dissolved in 30 mL of dichloromethane, and 1.4 g (10 mmol) of boron trifluoride diethyl ether solution was added dropwise. The reaction was allowed to proceed at room temperature for 1 h. The reaction was quenched with water, neutralized with sodium carbonate solution, extracted with dichloromethane / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 3.70 g of intermediate 7c was obtained by silica gel column chromatography, yielding 63%. The molecular weight was determined by mass spectrometry to be m / z = 587.3 [M]. + ].
[0092] Synthesis of intermediate 7d: 3.52 g (6 mmol) of intermediate 7c, 2.02 g (6 mmol) of intermediate 1a, 0.03 g (0.03 mmol) of tris(dibenzylacetone)dipalladium, 0.05 g (0.12 mmol) of tri-tert-butylphosphine, and 0.76 g (8 mmol) of sodium tert-butoxide were weighed and added to 20 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 120 °C. After cooling to room temperature, it was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 3.89 g of intermediate 7d, with a yield of 73%. The molecular weight was determined by mass spectrometry to be m / z = 888.5 [M]. + ].
[0093] Synthesis of Chemical 115: Replacing intermediate 1f with intermediate 7d in the synthesis of Chemical 2, under the same reaction conditions, yielded 0.95 g of the target product, 11% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 862.5 [M]. + ].
[0094] Synthesis Example 8: Synthesis of Chemical 145
[0095]
[0096] Synthesis of intermediate 8a: Intermediate 7a in the synthesis of intermediate 7b was replaced with 3,6-di-tert-butylcarbazole. Under the same reaction conditions, 4.46 g of the target product was obtained, with a yield of 89%. The molecular weight, determined by mass spectrometry, was m / z = 501.1 [M]. + ].
[0097] Synthesis of intermediate 8b: 5.0 g (10 mmol) of intermediate 8a was dissolved in 30 mL of anhydrous THF. Under nitrogen protection at -70 °C, 4.0 mL (2.5 M, 10 mmol) of n-butyllithium hexane solution was added dropwise. The reaction was allowed to proceed at low temperature for 0.5 h, then 1.8 g (10 mmol) of 9-fluorenone was added, and the reaction was allowed to proceed at low temperature for 1 h, followed by natural return to room temperature for 2 h. The reaction was quenched with water, extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. The solution was dissolved in 30 mL of dichloromethane, and 1.4 g (10 mmol) of boron trifluoride diethyl ether solution was added dropwise. The reaction was allowed to proceed at room temperature for 1 h. The reaction was quenched with water, neutralized with sodium carbonate solution, extracted with dichloromethane / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 4.22 g of intermediate 8b was obtained by silica gel column chromatography, yielding 72%. The molecular weight was determined by mass spectrometry to be m / z = 585.3 [M]. + ].
[0098] Synthesis of intermediate 8c: 5.85 g (10 mmol) of intermediate 8b, 4.14 g (10 mmol) of intermediate 2a, 0.45 g (0.5 mmol) of tris(dibenzylacetone)dipalladium, 0.88 g (4 mmol) of tri-tert-butylphosphine, and 1.44 g (15 mmol) of sodium tert-butoxide were added to 30 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 100 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Separation by silica gel column chromatography yielded approximately 4.21 g of intermediate 8c, with a yield of 66%. The molecular weight, determined by mass spectrometry, was m / z = 962.5 [M]. + ].
[0099] Synthesis of Chemical 145: Replacing intermediate 1f with intermediate 8c in the synthesis of Chemical 2, under the same reaction conditions, yielded 1.12 g of the target product, 12% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 936.5 [M]. + ].
[0100] Synthesis Example 9: Synthesis of Chemical 165
[0101]
[0102] Synthesis of intermediate 9a: 2.05 g (10 mmol) of m-di-tert-butylaniline, 2.53 g (10 mmol) of 3-bromo-5-tert-butylbenzofuran, 0.45 g (0.5 mmol) of tris(dibenzylacetone)dipalladium, 0.88 g (4 mmol) of tri-tert-butylphosphine, and 1.44 g (15 mmol) of sodium tert-butoxide were added to 30 mL of toluene. The mixture was purged under nitrogen protection and reacted overnight at 80 °C. After cooling to room temperature, the mixture was extracted with ethyl acetate / water, dried over anhydrous sodium sulfate, and concentrated by rotary evaporation. Approximately 2.11 g of intermediate 9a was obtained by silica gel column chromatography, yielding 56%. The molecular weight was determined by mass spectrometry to be m / z = 376.3 [MH].- ].
[0103] Synthesis of intermediate 9b: Replacing intermediate 2a in the synthesis of intermediate 8c with intermediate 9a, under the same reaction conditions, yielded 5.83 g of the target product, a yield of 63%, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 926.5 [M]. + ].
[0104] Synthesis of Chemical 165: Replacing intermediate 1f with intermediate 9b in the synthesis of Chemical 2, under the same reaction conditions, yielded 0.98 g of the target product, 11% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 900.6 [M]. + ].
[0105] Synthesis Example 10: Synthesis of Chemical 123
[0106]
[0107] Synthesis of intermediate 10a: Replacing 9-fluorenone with 10,10-dimethylanthrone in the synthesis of intermediate 8b, under the same reaction conditions, yielded 4.59 g of the target product, 73% yield, as a yellow solid. Mass spectrometry determined the molecular weight to be m / z = 628.7 [M]. + ].
[0108] Synthesis of intermediate 10b: Replacing intermediate 8b with intermediate 10a in the synthesis of intermediate 8c, under the same reaction conditions, yielded 6.32 g of the target product, a yield of 63%, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 1004.5 [M]. + ].
[0109] Synthesis of Chemical 123: Replacing intermediate 1f in the synthesis of Chemical 2 with intermediate 10b, under the same reaction conditions, yielded 1.27 g of the target product, 13% yield, as a yellow solid. Mass spectrometry analysis showed a molecular weight of m / z = 978.6 [M]. + ].
[0110] Device Examples:
[0111] The film layer function of the organic electroluminescent device involved is described below according to a preferred embodiment of the present invention.
[0112] The organic electroluminescent device described in this invention comprises an anode layer, a cathode layer, and at least one organic layer between the anode and the cathode. Alternatively, the organic layer may be a film layer composed of multiple layers of organic compounds. The organic layer may also contain inorganic compounds.
[0113] At least one organic layer in the organic electroluminescent device described in this invention is a light-emitting layer. Besides the light-emitting layer, the organic layer may also include other functional layers. For example, one or more hole injection layers, hole transport layers, or electron blocking layers may exist between the anode layer and the light-emitting layer. It is also feasible to have an exciton blocking layer or an intermediate layer with similar function between two light-emitting layers. Similarly, one or more hole blocking layers, electron transport layers, or electron injection layers may exist between the light-emitting layer and the cathode layer. It should be noted that these functional layers are not necessarily present.
[0114] The organic electroluminescent device described in this invention can be a fluorescent or phosphorescent device, or a hybrid fluorescent and phosphorescent device; it can be a device with a single light emission, or a device with multiple light-emitting units connected in series; it can be processed by vapor deposition or solution processing; it can be a bottom-emitting device or a top-emitting device. Furthermore, it can be a monochromatic light-emitting device, a mixed-color device, or a white light-emitting device.
[0115] The luminescent layer can contain multiple guest materials and multiple host materials. Guest materials can be fluorescent materials, phosphorescent materials, and / or thermally activated delayed fluorescence materials. Host materials refer to the matrix material that constitutes the vast majority of the components in the luminescent layer. Host materials doped with fluorescent materials are called "fluorescent hosts," and host materials doped with phosphorescent materials are called "phosphorescent hosts." It should be noted that the selection of host materials does not depend on their molecular structure, but rather on the matrix material that serves as the guest material.
[0116] The light-emitting layer is a mixture obtained by co-evaporation of the host material and the light-emitting material, wherein the doping concentration of the light-emitting material is 0.5% to 20% by weight.
[0117] The compounds of the present invention according to the above embodiments can be used in different organic layers. Preferably, the compounds of the present invention are used as luminescent materials in the luminescent layer of organic electroluminescent devices. The uses of the compounds of the present invention according to the above embodiments are also applicable to organic electronic devices.
[0118] These methods are generally known to those skilled in the art and can be applied to organic electroluminescent devices containing the compounds of the present invention without any inventive effort.
[0119] The following examples, namely Device Examples 1-12 and Comparative Examples 1-3, detail the application effects of the compounds of the present invention in organic electroluminescent devices, thereby verifying the technical progress and beneficial effects of the compounds of the present invention in the field. These examples and comparative examples are merely further elaborations of the present invention, but the present invention is not limited by technical conditions.
[0120] Device Examples 1-12: Fabrication of Organic Electroluminescent Devices Used as Light-Emitting Layer Materials
[0121] A 25mm × 75mm × 1.1mm thick glass substrate with an indium tin oxide (ITO) transparent electrode (anode) was ultrasonically cleaned in isopropanol for 5 minutes, followed by ultraviolet (UV)-ozone cleaning for 30 minutes. The ITO film thickness was 130nm. The cleaned glass substrate was mounted on the substrate holder of a vacuum evaporation apparatus, and the vacuum was evacuated to 1×10⁻⁵~1×10⁻⁶ Pa. A hole injection layer (HIL) HATCN with a thickness of 15nm was deposited on the ITO transparent conductive layer. A hole transport layer A (HTL) with a thickness of 60nm was then deposited on the hole injection layer. An electron blocking layer (EBL) with a thickness of 5nm was then deposited on the hole transport layer A. Finally, a light-emitting layer (EML) with a thickness of 20nm was co-deposited on the electron blocking layer. The light-emitting layer (EML) used a multi-source co-deposition method to deposit the light-emitting material BD and the host material BH, wherein the doping concentration of the light-emitting material was 2% by weight. To ensure the accuracy of the doping concentration of the luminescent material, the evaporation rates of the luminescent material and the host material need to be stabilized before the shielding plate is opened for multi-source co-evaporation. Then, a hole blocking layer (HBL) with a thickness of 5 nm is deposited on top of the luminescent layer. Next, an electron transport material (ETL) and lithium 8-hydroxyquinoline (Liq) with a thickness of 30 nm and a doping ratio of 1:1 are deposited on top of the hole blocking layer. Then, an electron injection electrode (EIL) Liq with a thickness of 1 nm is deposited on top of the ETL. Finally, a metallic cathode aluminum (Al) with a thickness of 100 nm is deposited on top of the EIL. The organic electroluminescent device structure of Example 1 is as follows. Figure 1 As shown, Figure 1 The stacking order and function of each functional layer are also shown. The molecular structure of the material used in OLED is shown in Table 1.
[0122] Table 1 Materials used in OLEDs
[0123]
[0124] The specific device structure of Device Example 1 is: ITO(130) / HATCN(15) / HTL(60) / EBL(5) / BH:Liq2(20, 2% by weight) / HBL(5) / ETL:Liq(30, 50% by weight) / Liq(1) / Al(100). It should be noted that the numbers in parentheses represent the film thickness (unit: nm).
[0125] The only difference between Device Examples 2 to 10 and Device Example 1 is that the compound 2 of the present invention used in the light-emitting layer is replaced with other compounds of the present invention, as detailed in Table 2.
[0126] The difference between Comparative Examples 1 to 3 and Device Example 1 is that the luminescent material in the organic electroluminescent device is changed to Comparative Compounds-1 to-3. The device performance test data are shown in Table 2.
[0127] The OLED was characterized using standard methods. For this purpose, the electroluminescence spectrum, current efficiency (measured in cd / A), power efficiency (measured in lm / W), and external quantum efficiency (EQE, measured as a percentage) were determined as a function of luminous density from the current / voltage / luminous density characteristic line (IUL characteristic line) exhibiting Lambertian emission characteristics. The required voltage V10 was determined at a current density of 10 mA / cm². Finally, EQE represents the external quantum efficiency at a current density of 10 mA / cm², T95 represents the operating time at which the device brightness decreases to 95% at a current density of 10 mA / cm², and the half-maximum width at half-maximum (FWHM) is the spectral width of the electroluminescence spectrum at the FWHM position at a current density of 10 mA / cm².
[0128] Table 2 Overview of OLED Device Performance
[0129]
[0130] As shown in Table 2, the EQE efficiencies of the devices using compounds 1-3 were 6.9%, 7.3%, and 7.4%, respectively. This is mainly due to the low quantum yield efficiency (PLQY) of the luminescent molecules and intermolecular aggregation. Aggregation also accelerates device aging and reduces device lifetime (ACS Appl. Mater. Interfaces 2018, 10, 30022-30028), resulting in shorter T95 lifetimes for the three comparative compounds. Using the molecules of this invention as dopants in the luminescent layer significantly improves the performance of the electroluminescent devices, particularly efficiency and lifetime. For example, device Example 9, fabricated using compound 145, achieved an EQE efficiency of 9.0%, a 30% improvement compared to Comparative Example 1. Simultaneously, its T95 lifetime reached 74 hours, a 60% improvement compared to Comparative Example 1. Furthermore, the full width at half maximum (FWHM) of the electroluminescence spectrum of the device was significantly reduced compared to the comparative examples. Devices with narrow half-peak and wide spectrum can not only improve their color purity, but also improve their light extraction efficiency in top-emitting devices, which is beneficial to further improve the performance of their corresponding top-emitting devices.
[0131] Photophysical data
[0132] The comparative compounds 1-3 and the molecules of the synthesis examples, such as compounds 2 and 7, were measured using a spectrophotometer manufactured by Hitachi High-Tech Co., Ltd. A 100 nm thick thin film of luminescent material and BH was deposited onto a quartz plate, with the luminescent material doping concentration being 2% by weight. The film sample with the quartz plate was irradiated with 360 nm excitation light at room temperature (300 K) to measure the fluorescence spectrum, and the full width at half maximum (FWHM) was obtained, as shown in Table 3. Then, the luminescence quantum efficiency (PLQY) of the samples was measured using an absolute PL quantum yield measurement device manufactured by Hamamatsu Photonics Co., Ltd.
[0133] Table 3. Photophysical properties
[0134] sample Full width at half maximum (nm) PLQY (%) Compare compound 1 28.4 78 Compare compound 2 26.3 81 Compare compound 3 27.8 83 2 22.2 94 Transformation 7 22.5 93 Transformation 8 21.7 95 50 19.2 97 52 20.1 94 59 21.0 94 115 22.3 95 123 21.3 93 145 21.2 95 165 23.0 96
[0135] Table 3 shows that the fluorescence efficiency (PLQY) of the thin film with 2% doping of compound-1 in BH is 78%; its fluorescence spectrum has a full width at half maximum (FWHM) of 28.4 nm, indicating that its device has low color purity and low device efficiency.
[0136] The luminous efficacy (PLQY) of the BH-doped films of Comparative Compound 2 and Comparative Compound 3 were 81% and 83%, respectively, showing a certain improvement; the full width at half maximum (FWHM) were 26.3 and 27.8 nm, respectively, which were still relatively wide.
[0137] The 2% BH-doped thin film of the compound of this invention has a half-width at half-maximum (FWHM) ≤ 23 nm, significantly smaller than that of the comparative compounds, which is beneficial for obtaining high color purity in the device spectrum. Simultaneously, the doped film of the compound of this invention has a PLQY ≥ 93%, and its high luminous efficiency significantly improves the device efficiency. The improvement in luminous efficiency and the reduction in FWHM are mainly due to the rigid planar structure constructed in this invention, which suppresses non-radiative decay of molecules, while the steric hindrance of the quaternary carbon substituents effectively suppresses intermolecular aggregation quenching.
Claims
1. A fused heterocyclic compound, characterized in that, The fused heterocyclic compounds are selected from the following structures: 。 2. An organic electroluminescent device, characterized in that, The organic electroluminescent device includes an anode, a cathode, and at least one organic thin film located between the anode and the cathode, the organic thin film containing the compound of claim 1.
3. The organic electroluminescent device according to claim 2, characterized in that, The organic thin film includes any one or at least two combinations of a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, an exciton blocking layer, a hole blocking layer, an electron transport layer, and an electron injection layer, and at least one of the light-emitting layers contains the compound of claim 1.
4. The organic electroluminescent device according to claim 2 or 3, characterized in that, The compound is used as a fluorescent material for the light-emitting layer in organic electroluminescent devices.
Citation Information
Patent Citations
Organic electroluminescent material and application thereof
CN116444549A
Organic semiconductor luminescent compound and application thereof
CN116804023A
Condensed heterocyclic compound, application thereof and organic electroluminescent device containing compound
CN117263964A
Polycyclic aromatic compound, organic electroluminescent element, display device, and lighting device
CN117886836A
